Pola konsumsi pangan dan tingkat ketahanan pangan rumah tangga di Kabupaten Kampar Provinsi Riau - Rahmadya Saputri; Lily Arsanti Lestari; Joko Susilo (Jurnal Gizi Klinik Indonesia, 2016)
Background: Food consumption is a major factor to fulfill the nutritional needs of a person. Food consumption is influenced by several factors, such as the level of income, food availability, public awareness toward nutrition, and socio-cultural factors. Riau Province is one of the provinces that the food consumption is still relatively low and Kampar Regency occupies a very high position in the food insecurity index and hunger vulnerability index. There is 49.21% of the population that could potentially be food shortages. This is supported by the occurrence of nutritional problems in communities associated with the availability of food, low purchasing power and the inability to gain access to nutritious food.Objective: To identify the patterns of food consumption and family food security in Kampar regency in Riau province.Method: The study was an observational research with cross sectional design. Samples are a family in Kampar regency as many as 105 families selected by using cluster sampling conducted in August-September 2015. Statistical analysis was performed by chi-square test and logistic regression.Results: The statistical analysis shows that the majority of respondents had food consumption patterns with the category of unfulfilled as 64.77% and for the category of food security as 60.96% was in the category of food insecure. The results of chi-square statistical test showed that there was a significant correlation between food consumption patterns to family food security in Kampar regency Riau Province (p0,000). The results of the bivariate analysis it is known that there was a significant correlation between the variables of the number of family member, food access, food expenses, energy consumption and protein consumption to the level of family food security in Kampar regency of Riau province indicated by a value of p <0.05.Conclusion: There is a significant correlation between the patterns of food consumption toward family food security in Kampar regency Riau province. There is a significant correlation between the external variables and family food security level in Kampar regency Riau Province.